Racial disparities in overall survival among renal cell carcinoma patients with young age and small tumors. (29th December 2015) - Schwartz, Kendra; Ruterbusch, Julie J.; Colt, Joanne S.; Miller, David C.; Chow, Wong‐Ho; Purdue, Mark P.
Abstract: We examined the overall survival of a population‐based cohort of black and white patients with renal cell carcinoma (RCC) to better understand the paradox of poorer RCC survival despite more frequent diagnosis at lower stage among blacks. Renal cell carcinoma patients (699 white, 252 black) diagnosed between 2002 and 2007 in metropolitan Detroit were followed for vital status in the Detroit Surveillance, Epidemiology and End Results (SEER) registry. Hazard ratios (HR) of death for black versus white race and 95% confidence intervals (CIs) were calculated using Cox proportional hazard models stratified by demographic and prognostic factors, and in models successively adjusted for clinical factors, comorbidities, and socioeconomic factors. Mean follow‐up time was 88.4 months for white patients and 89.6 months for black patients ( P = 0.49), with 202 white deaths and 89 black deaths ( P = 0.06). While black race was weakly associated with poorer overall survival ( P = 0.053), black patients <65 years at diagnosis or with tumors< 4 cm in size had significantly poorer survival than their white counterparts (HR = 1.46, 95% CI 1.06–2.01 and HR = 2.15, 95% CI 1.51–3.06, respectively). The racial disparities within these two subgroups were minimally affected by adjustment for clinical/treatment factors (HR = 1.49, 95% CI 1.01–2.19 and HR = 1.95, 95% CI 1.27–2.99), but were substantially reduced when renal‐relevant comorbidities were added (HR = 1.30, 95% CI 0.89–1.91 and HR = 1.76, 95% CI 1.16–2.66). After further adjustment for socioeconomic factors, the survival disparities were essentially null (HR = 1.14, 95% CI 0.71–1.85 and HR = 1.15, 95% CI 0.67–1.98). In this population‐based sample of RCC patients, younger black patients and those with small tumors had poorer overall survival than whites. The disparity was explained primarily by racial differences in renal‐relevant comorbidities, particularly chronic renal failure, and socioeconomic deprivation. Future research should focus on younger patients and those with smaller tumors to better understand how these factors may contribute to the survival disparity. Abstract : Black RCC patients, especially those under age 65 years and those with tumors 4 cm or less in size, experience poorer survival compared to white patients. This survival difference is mainly attributable to racial differences in comorbidities, particularly chronic renal failure, and factors associated with low socioeconomic status.